Site-specific variations in surface structure and Young's modulus of human hair surfaces at the nanometer scale as induced through bleach treatment. (February 2022) - Humphry, Rose; Wang, Nan; Durkan, Colm
Abstract: The effect of bleach treatments on the morphology and mechanical properties of hair surfaces was measured at the nanometer scale using atomic force microscopy. We used an ultrahigh-precision relocation technique to observe the variations in these properties at precise locations on hair surfaces in their virgin state and then after each of the two bleach treatments, to rule out position-dependent fluctuations. We demonstrate that statistically significant variations in roughness and Young's modulus are observed as a result of exposure to bleach, which is known to disrupt the disulfide linkage network throughout the fiber. The rate at which surface roughness changes increased with the number of treatments, with very little effect seen after 10 min, and an increase of up to 65% was observed after a further 10 min. The Young's modulus decreased by up to 40% after each treatment. We also investigate micropores and show that they are subsurface, but revealed through bleaching, and oriented along the direction of the hair shaft with a characteristic aspect ratio. This work demonstrates the profound effect bleaching has on the molecular structure of hair, which manifests as changes in morphology and stiffness, and this should be taken into account in the formulation of future hair-care products.